2005
DOI: 10.1021/ic051077x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Palladium and Platinum Tri-tert-Butylphosphine Groups to Re−Sn and Re−Ge Bonds

Abstract: The reaction of Re2(CO)8[mu-eta2-C(H)=C(H)Bu(n)](mu-H) with Ph3SnH at 68 degrees C yielded the new compound Re2(CO)8(mu-SnPh2)2 (10) which contains two SnPh2 ligands bridging two Re(CO)(4) groups, joined by an unusually long Re-Re bond. Fenske-Hall molecular orbital calculations indicate that the bonding in the Re2Sn2 cluster is dominated by strong Re-Sn interactions and that the Re-Re interactions are weak. The 119Sn Mössbauer spectrum of 10 exhibits a doublet with an isomer shift (IS) of 1.674(12) mm s(-1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 68 publications
4
43
0
Order By: Relevance
“…In previous studies it has been shown that the bonding of PtðPBu t 3 Þ groupings to homo-and heteronuclear metal-metal bonds can be quite complex particularly when more than one PtðPBu t 3 Þ grouping is involved [8,12,26]. To develop a better understanding of the metal-metal bonding in 9 and to compare it with that in 7, a Fenske-Hall molecular orbital analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies it has been shown that the bonding of PtðPBu t 3 Þ groupings to homo-and heteronuclear metal-metal bonds can be quite complex particularly when more than one PtðPBu t 3 Þ grouping is involved [8,12,26]. To develop a better understanding of the metal-metal bonding in 9 and to compare it with that in 7, a Fenske-Hall molecular orbital analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…(1)-(3) [3,6,7]. Bridging tin ligands, SnPh 2 [3,[6][7][8][9][10][11], SnPh [3,7], and even naked Sn [10] are commonly formed by the cleavage of 1-3 of the Ph groups from the tin atom. …”
Section: Introductionmentioning
confidence: 99%
“…ME spectroscopy was carried out in transmission geometry as described previously [4,5], using a 10 mCi Ba 119m SnO 3 source at room temperature. Spectrometer calibration was effected using a 57 Co (Rh) source in conjunction with a room temperature a-Fe absorber.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, a significant difference between the two Re-Pd bond lengths was observed in the compound [(g 5 -C 4 H 4 BPh)(CO) 3 RePd] 2 (2.866(1) and 2.666(1) Å) [25]. The Re-Pd bond distances are shorter than those in (g 5 -7-CB 10 H 11 ) (CO) 3 RePd(dppe) (2.7858(4) Å) [26], Re 2 (CO) 8 (l-SnPh 2 ) [Pd(PBu t ) 3 ] 2 (2.8580(5) Å) [27] and [NEt 4 ][Re 7 (CO) 21 {Pd(g 3 -PhC 3 -H 4 )}(C)] (2.872(5) Å) [28].…”
Section: Distances (å) Angles (°)mentioning
confidence: 91%
“…Other known examples are Cp 2 (CO) 4 MnPd(l-C@CHPh) MnPd(l 3 -C@CHPh)(dppe) [29], [Mn 2 Rh 2 (l-CC 6 H 5 )(l 3 -CC 6 H 5 )(l-CO) 3 (CO) 3 (g 5 -C 5 H 5 ) 2 ], [Mn 3 Rh 2 (l-CC 6 H 5 ) 2 (l 3 -CC 6 H 5 )(l-Cl)(l-CO) 3 (CO) 2 (g 5 -C 5 H 5 ) 3 ], [Re 2 Rh 2 (l-CC 6 H 5 )(l 3 -CC 6 H 5 )(l-CO) 3 (CO) 3 (g 5 -C 5 H 5 ) 2 ] [11] and Pd 2 Re 2 (CO) 8 (l-SnPh 2 ) 2 (PBu t ) 2 [27,30]. Moreover, the presence of two different coordinated vinylidene ligands in one molecule has been reported previously only for the analogous manganese complex Cp 2 (CO) 4 MnPd(l-C@CHPh)MnPd(l 3 -C@CHPh)(dppe) [29] and the cluster Cp ⁄ IrOs 3 (CO) 9 (l 4 -C@CHPh)(l 3 -C@CHPh), where one vinylidene unit is bounded to all four metal atoms and the second one to two osmium atoms and the iridium atom [31].…”
Section: Distances (å) Angles (°)mentioning
confidence: 99%